Cyclic microwave assisted synthesis of Sb2S3 dumb-bells using polyvinylpyrrolidone as a template and splitting agent - Jutarat Kavinchan (2018)
Antimony sulfide (Sb2S3) was successfully synthesized from antimony chloride (SbCl3) and sodiumthiosulfate (Na2S2O3) in ethylene glycol (EG) containing different polyvinylpyrrolidone (PVP) masses under cyclic microwave radiation. XRD and SEM show that the products were orthorhombic Sb2S3nanorods forming the dumb-bells. TEM study reveals Sb2S3single-crystal nanorods, growing along the [001] direction. The dumb-bell formation is also proposed, according to the splitting ends and a middle tie-up. Its direct band gap, calculated from UV-visible absorption, is 1.52 eV. © 2010 Elsevier B.V.